Actuators: Programmable 3D Shape Changes in Liquid Crystal Polymer Networks of Uniaxial Orientation (Adv. Funct. Mater. 37/2018) - Yu, Li; Shahsavan, Hamed; Rivers, Geoffrey; Zhang, Che; Si, Pengxiang; Zhao, Boxin (Advanced functional materials, 2018)
3D programmable materials offer an attractive platform for designing smart robotic devices. In article number 1802809, Boxin Zhao and co‐workers report the mechanical programming of 3D shape changes in liquid crystal polymer networks (LCNs) without the need of spatially modulating the orientation of liquid crystals. The process is promising for designing 3D programmable LCN actuators with complex geometries (film or fiber), and deformation profiles (buckle, helix, horn).